2007
DOI: 10.1086/524359
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Galactic Bar Length with Amplitude and Density as Evidence for Bar Growth over a Hubble Time

Abstract: plitudes. The long bars also correlate with an increased density in the central parts of the disks, as measured by the luminosity inside divided by the cube of this radius in kpc. Because denser galaxies evolve faster, 0.25R 25 these correlations suggest that bars grow in length and amplitude over a Hubble time, with the fastest evolution occurring in the densest galaxies. All but three of the sample have early-type flat bars; there is no clear correlation between the correlated quantities and the Hubble type.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 22 publications
19
60
0
Order By: Relevance
“…The length is the radius of the maximum ellipticity, r ε . As an upper limit of bar length, Erwin & Sparke (2003) and Erwin (2005 have used the first minimum in the ellipticity profile after r ε , named as L bar . However, as discussed in Michel- Dansac & Wozniak (2006), the location and value of such a minimum depends on the galaxy inclination and/or the real non-axisymmetric shape of the disk and the type of bar profiles, which is obvious also from the S 4 G images.…”
Section: Estimation Of Bar Lengths and Ellipticitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The length is the radius of the maximum ellipticity, r ε . As an upper limit of bar length, Erwin & Sparke (2003) and Erwin (2005 have used the first minimum in the ellipticity profile after r ε , named as L bar . However, as discussed in Michel- Dansac & Wozniak (2006), the location and value of such a minimum depends on the galaxy inclination and/or the real non-axisymmetric shape of the disk and the type of bar profiles, which is obvious also from the S 4 G images.…”
Section: Estimation Of Bar Lengths and Ellipticitiesmentioning
confidence: 99%
“…15 and 16 (see also Table 3), where the distributions of bar strengths and lengths are shown separated for the different bar families. Erwin (2005) concluded that strong (SB) and weak (SAB) bars hosted by early-type galaxies differ primarily in ellipticity, being very similar in size, while SB bars in late-type spiral galaxies are twice as large as SAB bars. We observe that SB, SAB, SAB, and SAB bars differ in ellipticity as well as in A a difference between weak and strong bars for the bar sizes, as visually categorized: SB and SAB galaxies are ∼10−15% longer relative to the disk size.…”
Section: Bar Parameters and The Family Classmentioning
confidence: 99%
See 2 more Smart Citations
“…Elmegreen et al (1990) reported an increased fraction of bars in groups and clusters, but more recent work (Barazza et al 2009;Li et al 2009;Aguerri et al 2009) has found little or no variation of bar fraction with environment. It is also possible that the bar fraction could be changing with time; different groups disagree (Jogee et al 2004;Sheth et al 2008), probably because observations of galaxies at significant look-back times are subject to systematic difficulties due to band-shifting and changing spatial resolution (see also Elmegreen et al 2007).…”
Section: Frequency Of Barsmentioning
confidence: 99%